Proteogenomics-guided functional venomics resolves the toxin arsenal and activity of Deinagkistrodon acutus venom - Avella, Ignazio; Schulte, Lennart; Hurka, Sabine; Damm, Maik; Eichberg, Johanna; Schiffmann, Susanne; Henke, Marina; Timm, Thomas; Lochnit, Günther; Hardes, Kornelia; Vilcinskas, Andreas; Lüddecke, Tim; et al. (My University, 2024)
Snakebite primarily impacts rural communities of Africa, Asia, and Latin America. The sharp-nosed viper (Deinagkistrodon acutus) is among the snakes of highest medical importance in Asia. Despite various studies on its venom using modern venomics techniques, a comprehensive understanding of composition and function of this species' venom remains lacking. We combined proteogenomics with extensive bioactivity profiling to present the first genome-level catalogue of D. acutus venom proteins and their exochemistry. Our analysis identified an unusually simple venom containing 45 components from 20 distinct protein families. Relative toxin abundances indicate that C-type lectin and C-type lectin-related protein (CTL), snake venom metalloproteinase (svMP), snake venom serine protease (svSP), and phospholipase A2 (PLA2) constitute 90 % of the venom. Bioassays targeting key aspects of viperid envenomation showed considerable concentration-dependent cytotoxicity, particularly in kidney and lung cells, and potent protease and PLA2 activity. Factor Xa and thrombin activities were minor, and no plasmin activity was observed. Effects on haemolysis, intracellular calcium (Ca2+) release, and nitric oxide (NO) synthesis were negligible. Our analysis provides the first holistic genome-based overview of the toxin arsenal of D. acutus, predicting the molecular and functional basis of its life-threatening effects, and opens novel avenues for treating envenomation by this highly dangerous snake.
Keywords: ddc:630